2010
DOI: 10.1111/j.1540-8167.2009.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of the St. Jude Medical Riata Defibrillation Lead in a Large Patient Population

Abstract: During the follow-up of the 15,387 patients with Riata leads, the incidence of AEs which included perforation, dislodgement, conductor fraction and insulation damage was low and within the range of what is considered clinically acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
1
29
2
1
Order By: Relevance
“…8,10 Compared with these data, the lead failure rate was 20-times to 100-times higher as reported by the manufacturer (0.63%) 7 and published in 2 performance articles of the Riata lead family (0.13% and 0.21%, respectively). 11,12 The main reason for this discrepancy could be explained by the definition of adverse events that were defined as those that required lead revision, extraction, or replacement. Without systematic fluoroscopically screening, the rate of conductor externalization was obviously underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 Compared with these data, the lead failure rate was 20-times to 100-times higher as reported by the manufacturer (0.63%) 7 and published in 2 performance articles of the Riata lead family (0.13% and 0.21%, respectively). 11,12 The main reason for this discrepancy could be explained by the definition of adverse events that were defined as those that required lead revision, extraction, or replacement. Without systematic fluoroscopically screening, the rate of conductor externalization was obviously underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported a very low incidence of lead insulation damage at 0.16% in 6,405 patients with a median follow-up of 24 months [7]. Another large series involving 15,378 patients with a median follow-up period of 13.5 months reported insulation defects of the order of 0.21% [6]. These studies were limited by the way insulation defects were ascertained and no systematic fluoroscopy was used.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported various electrical abnormalities associated with lead externalization such as pacing impedance rise, increased capture threshold or inappropriate ICD shocks due to noise [2,5]. Earlier studies have shown a low rate of lead insulation failure (< 1%) but these studies were limited due to the way insulation failure were analyzed (no consistent fluoroscopy) or shorter period of follow up [6,7]. A recent large study by Hauser et al [8] reported an alarming number of deaths in patients implanted with Riata ® and Riata ® ST leads primarily associated with failed defibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…Riata leads have a unique multi-lumen design in which one or two coil conductors and a ring conductor are packed independently into each silicon cavity surrounding a tip conductor. Recently, some instances of insulation damage in the Riata family have been reported (1)(2)(3)(4). An information report from St. Jude Medical Co. indicated that externalized conductors may result from relative motion of conductor cables within the silicon insulation lumen, referred to as "inside-out" abrasion (5).…”
Section: Insulation Defects In Riata Leadsmentioning
confidence: 99%
“…Over 200,000 Riata and Riata ST ICD leads (St. Jude Medical, Sylmar, CA, USA) were implanted worldwide between 2002 and 2010. Recently, it has been announced that insulation defects are a special problem associated with these leads in Western countries, although the precise incidence and clinical details of the problems have not yet been clarified (1)(2)(3)(4). The conductor cables in the leads are prone to erode the silicone insulation and project outside of the lead body.…”
Section: Introductionmentioning
confidence: 99%